New Possible Earthquake Precursor and Initial Area for Satellite Monitoring - Vasilev, Atanas; Tsekov, Milen; Petsinski, Petar; Gerilowski, Konstantin; Slabakova, Violeta; Trukhchev, Dimitar; Botev, Emil; Dimitrov, Orlin; Dobrev, Nikolai; Parlichev, Dimitar (Frontiers in Earth Science, 2021)
The main aim of this work is to present precursory earthquake phenomena preceding an offshore earthquake near the Bulgarian Black Sea coast. We also propose an earthquake forecasting experiment, based on the following four hypotheses: 1. The change of the methane emission of shallow horizons are related to crustal strain changes preceding earthquakes in the region; 2. Extreme change of the activity of underwater methane seepages appears immediately before nearby earthquakes; 3. Shallow water methane seepages activity can be monitored by remote sensing; 4. Satellites can register effects from an extreme increase in their emissions. Our results may contribute to the identification of a possible new earthquake precursor, to remote sensing search and monitoring of fluid emissions from shallow methane and search of areas with suitable conditions for earthquake forecasting experiments as Zelenka area near cape Kaliakra, Black Sea. The idea was born after the only planned observation of seepages activity after an offshore earthquake when divers documented 3-5 times decrease of the area with active seepages. Additional evidence is based on earthquake data; satellite photos showed the distribution of lighter colored contaminants started from Zelenka; model estimations of the wave highs and current velocities. Incident studies of the seepages activity give additional information about local geology; discussed processes; the reliability of the evidence; parameters of a future monitoring of seepages and earthquakes.